Plurilingual Pedagogy in the Arabian Peninsula Transforming and Empowering Students and Teachers - Coelho, Daniela; Gharibian Steinhagen, Telma (Taylor & Francis, 2023)
This edited collection explores plurilingual education in the unique English medium instruction (EMI) context of the Arabian Peninsula. The book argues that integrating a plurilingual pedagogy alongside current EMI in the region could enhance students' learning and contribute to a language policy that embraces linguistic diversity while fostering regional identity. It brings together the work of experts in Arabic and English language policy and planning, presenting empirical research relating to plurilingual pedagogical practices within the region. The book offers a range of recommendations for educators on how to integrate plurilingual pedagogies in classroom teaching. This becomes more important since many educators in the region are non-Arabic speakers and are teaching students with diverse linguistic backgrounds through English. With a holistic and interdisciplinary approach to the linguistic landscape in the Arabian region, this book will be of great interest to researchers, scholars, and students in the fields of applied linguistics, language education, teacher education, and EMI.